Outsourcing decisions – the case of parallel production. Issue 8 (29th July 2014) - Nordigården, Daniel; Rehme, Jakob; Brege, Staffan; Chicksand, Daniel; Walker, Helen
Abstract : Purpose: – The purpose of this paper is to investigate an underexplored aspect of outsourcing involving a mixed strategy in which parallel production is continued in-house at the same time as outsourcing occurs. Design/methodology/approach: – The study applied a multiple case study approach and drew on qualitative data collected through in-depth interviews with wood product manufacturing companies. Findings: – The paper posits that there should be a variety of mixed strategies between the two governance forms of "make" or "buy." In order to address how companies should consider the extent to which they outsource, the analysis was structured around two ends of a continuum: in-house dominance or outsourcing dominance. With an in-house-dominant strategy, outsourcing complements an organization's own production to optimize capacity utilization and outsource less cost-efficient production, or is used as a tool to learn how to outsource. With an outsourcing-dominant strategy, in-house production helps maintain complementary competencies and avoids lock-in risk. Research limitations/implications: – This paper takes initial steps toward an exploration of different mixed strategies. Additional research is required to understand the costs of different mixed strategies compared with insourcing and outsourcing, and to study parallel production from a supplier viewpoint. Practical implications: – This paper suggests that managers should think twice before rushing to a "me too" outsourcing strategy in which in-house capacities are completely closed. It is important to take a dynamic view of outsourcing that maintains a mixed strategy as an option, particularly in situations that involve an underdeveloped supplier market and/or as a way to develop resources over the long term. Originality/value: – The concept of combining both "make" and "buy" is not new. However, little if any research has focussed explicitly on exploring the variety of different types of mixed strategies that exist on the continuum between insourcing and outsourcing.